Study Analyzing the Role of Nomophobia Tendencies with Friendship Quality: A Study of Indonesian College Students - Regina, Agatha; Garvin Goei (HM Publisher, 2024)
Introduction: Smartphones have become a primary need in the technological era. However, anxiety can arise when individuals are not near their smartphones, which is known as nomophobia. This study aims to determine the relationship between nomophobia tendencies and friendship quality. Methods: This research uses a quantitative correlational method with a cross-sectional design. A sample of 371 students aged 18-25 years in Indonesia was taken using non-probability convenience sampling. Data were collected using the nomophobia questionnaire (NMP-Q) and the McGill Friendship Questionnaire-Friend's Functions (Short) (MFQ-FFS) questionnaires. Results: The results showed that there was a significant relationship between nomophobia tendencies and friendship quality (r = 0.294 and p = 0.000). The higher an individual's nomophobia tendencies, the higher the quality of friendships formed. Conclusion: Nomophobia has a positive relationship with friendship quality. This shows that individuals with nomophobia tendencies find it easier to establish and maintain friendly relationships.